Effects of Soil Textures, Soil Settlements, and Soil Water-Holding Capacity on Landslides: An Experimental Study for Science Teachers - Donna Hembra Gabor (Universitas Pendidikan Indonesia, 2023)
Experimentation is a contributing factor to the interest and meaningful learning of Science. In Geology and Earth Science, the effects of soil textures, settlements, and water-holding capacity are parameters for landslides in Barotac Viejo and other flooded areas. Landslides are triggered during heavy rainstorms, causing severe property damage and casualties. This experimental study aims to determine how these parameters are factors for landslides and give accurate information to Science teachers. The study uses two methods to provide ease and continuity of measurements and settings using the Fourier Transform Infrared(FTIR) spectroscopy in analyzing the soil textures. The Imhoff cone instrument is for the settling and water-holding capacity of the soil. FTIR Soil analysis reveals that contents of clay and organic matter directly affect soil water-holding ability due to the larger surface area. A landslide-prone zone has a lesser settling time except for the sand that settles fastest due to larger masses. This study is crucial for science teachers teaching geology and earth sciences besides forecasting and preventing geohydrological processes and developing better landslide warning strategies to mitigate risks and reduce socioeconomic damage.